Clustering shrimp farming to promote traceability and certification: IPSR Innovation Profile - Narayanan, Sudha; Kabir, Razin; Belton, Ben; Hernandez, Ricardo; Hossein, P. (CGIAR System Organization, 2024)
Clustering shrimp farming for traceability and certification strengthens backward linkages with farmers via aggregation, disintermediation, technology transfer, and enabling certification. All innovation partners organize shrimp farmers with contiguous ponds into groups of 20-25. Farmers in a cluster coordinate stocking and harvest of specific species of shrimp. All three innovation partners have similar approaches but vary somewhat in terms of the specific support and requirements of the cluster. ACI Agrolink hopes to buy back shrimp for its processing plant and aims to bundle this with providing Input credit to shrimp farmers who buy ACI Animal Health’s feed and insurance. In the BSFF (Bangladesh Shrimp and Fish Foundation) model, shrimp farmers commit to monoculture and are provided SPF-PL (Specific Pathogen Free Post-Larvae), cluster level credit from designated banks, and a buyback arranged with specific processing firms. In the DoF (Department of Fisheries) model, farmers are persuaded to deepen their ponds to reduce water temperature variability that can trigger disease outbreaks, and facilitate increased stocking densities as a precondition to participate. For clusters that achieve some of these essential conditions, the DoF extends financial support to the cluster.